Organización contable a la empresa créditos F & F del cantón Marcabelí – El Oro. Periodo abril – junio 2022 - Alvarado Orozco, Cynthia Fernanda (2023)
The research work titled "Accounting Organization for F & F Credits Company in Marcabelí Canton - El Oro. April - June 2022 Period" was developed as a requirement for obtaining a degree in Accounting and Auditing, following the regulations set forth by the Academic Regime Regulations of the Universidad Nacional de Loja. The main purpose of this project was to assess the economic and financial situation of the company by means of accounting organization and provide the business owner with accurate and timely information through the preparation of financial statements and the application of financial indicators. These measures aimed to facilitate sound decision-making processes geared towards strengthening and expanding the organization. Based on the proposed objectives and in order to fulfill them, the business was analyzed using information provided by the owner. This information served as a reference for designing a classified and coded chart of accounts, aligned with the daily economic activities. Additionally, a chart of accounts manual was developed to describe, detail, and specify concepts, debits, and credits for assets, liabilities, equity, income, costs, and expenses. Subsequently, inventory control was carried out through the physical counting and verification of assets, rights, and obligations. The process resulted in determining assets of $616,824.84, liabilities of $35,165.74, and equity of $581,659.10. It involved structuring the opening balance sheet after preparing the initial inventory, followed by creating auxiliary records of purchases and sales based on the source documentation. The information was then recorded in the general journal and consolidated in the general ledger and trial balance. Adjustments were made to prepare the financial statements. The outcome in the Balance Sheet shows assets of $685,431.56, liabilities of $93,566.07, and equity of $581,865.49. In the Income Statement, revenues of $19,455.95 and expenses of $9,249.56 were reflected, resulting in a net income of $10,206.39 for the period. By using liquidity indicators, an adequate current ratio of 5.15 was obtained, demonstrating that current assets are enough to meet short-term obligations to third parties. Moreover, profitability indicated a return on assets of 1.49% and a return on equity of 1.72%, suggesting that despite the significant amount of assets, a considerable profit has not been generated. This underscores the need for better accounting organization to enhance control and decision-making.